Fourth Five Year Plan 1969-74 Government of Haryana - Planning Commission (Planning Commission, 1969)
On 1st April, 1969, the region now forming Haryana State completed nearly two and a half years of its formal existence. The State has an area of 43,869 sq. kms. and on the eve of the start of the Fourth Plan, the projected population of the State would be 99 lakhs. In the North, Haryana is bounded by the Shivalik range and the river Yamuna forms the boundary in the East.
Government of Haryana, Planning Department